Interleukin‐1 inhibition facilitates recovery from liver injury and promotes regeneration of hepatocytes in alcoholic hepatitis in mice. (27th April 2017) - Iracheta‐Vellve, Arvin; Petrasek, Jan; Gyogyosi, Benedek; Bala, Shashi; Csak, Timea; Kodys, Karen; Szabo, Gyongyi
Abstract: Background & Aims: Inflammation and impaired hepatocyte regeneration contribute to liver failure in alcoholic hepatitis (AH). Interleukin (IL)‐1 is a key inflammatory cytokine in the pathobiology of AH. The role of IL‐1 in liver regeneration in the recovery phase of alcohol‐induced liver injury is unknown. Methods: In this study, we tested IL‐1 receptor antagonist to block IL‐1 signalling in a mouse model of acute‐on‐chronic liver injury on liver inflammation and hepatocyte regeneration in AH. Results: We observed that inhibition of IL‐1 signalling decreased liver inflammation and neutrophil infiltration, and resulted in enhanced regeneration of hepatocytes and increased rate of recovery from liver injury in AH. Conclusion: Our novel findings suggest that IL‐1 drives sustained liver inflammation and impaired hepatocyte regeneration even after cessation of ethanol exposure.